Eksplorasi E-Governance: Menjawab Tantangan Implementasi E-Commerce Era VUCA di Indonesia - Astuti, Ismaya Indri; Sulisman, Alya Nurayu; Br Tarigan, Sri Ropika Dana (PUBLICNESS: Journal of Public Administration Studies, 2023)
Digital transformation has emerged as a key driver in realizing Indonesia's golden ambitions by 2045. The digital economy stands out as a primary sector experiencing significant growth, particularly in the realm of electronic commerce or E-Commerce. The growth of E-Commerce in Indonesia not only promises opportunities but also poses complex challenges amidst the dynamics of the VUCA era (Volatility, Uncertainty, Complexity, and Ambiguity). This qualitative research, utilizing a descriptive approach, draws data from literature studies. The study aims to analyze the pivotal role of E-Governance in creating a conducive environment for digital economic growth while addressing the complex challenges arising from rapid changes and uncertainties in the VUCA era. The presence of E-Commerce in Indonesia has created legal and regulatory uncertainties to navigate the disruptions in the digital market. Swift changes in information and technology raise concerns about data security among the public. The exploration of E-Governance is framed within three main elements: support, capacity, and value. These elements collectively address how E-Governance is utilized to confront the challenges in the E-Commerce ecosystem in the VUCA era in Indonesia.